KAMPANYE SOSIAL MENGGANTI KANTONG PLASTIK DENGAN TAS BELANJA BAGI IBU RUMAH TANGGA DI KOTA PALEMBANG - gilang harka; Husni Mubarat; Mukhsin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract: Plastic is widely used as packaging because it has many advantages and general properties such as being resistant to chemicals, insulating against heat and electricity, light and flexible. At this time, people in the city of Palembang still find it difficult to limit the use of plastic bags. It is hoped that public awareness of the negative impacts can contribute more by carrying shopping bags that can be used many times. Therefore, according to the designer, shopping bags of various types can be made wrong. One solution to reduce the use of plastic bags in Palembang City.